WHY DID THE STUDENTS MAKE MISTAKES IN SOLVING DIRECT AND INVERSE PROPORTION PROBLEM? - Irfan, Muhammad; Nusantara, Toto; Subanji, Subanji; Sisworo, Sisworo (Universitas Negeri Malang, 2018)
The purpose of this study is to describe the student's difficulties in solving direct and inverse proportion problem. This research uses explorative qualitative research type. The subject of this research is the second semester student of Mathematics Education Study Program in East Java. Subjects were selected based on purposive sampling. The findings of this study are 86% of students are wrong in solving the problem of inverse proportion, 28% of students are wrong in solving direct proportion problem, and 91% of students are wrong in solving both problems in a single question. Then, the students who made mistakes in solving the problem were chosen purposively for interview. The finding in this research is the student(1) do not understand the use of variables, (2) do not understand the use of formulas, (3) do not understand the key phrases on the problem, (4) Difference in ratio, fractional, and division, (5) do not understand the problem, (6) do not understand simplification of division, and (7) do not interpret proportion relation correctly.